Chemical Investigation of the seeds of Glircidia maculata - Sreedevi, E.; Rao, J.T. (Asian Journal of Chemistry, 2010)
The reducing sugars and proteins have been analysed from the seeds of Glircidia maculata. The seeds having high nutritional properties are used in cattle feed industries.